2011
DOI: 10.1111/j.1479-8298.2011.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating behavior and contact pheromones of Batocera horsfieldi (Hope) (Coleoptera: Cerambycidae)

Abstract: The mating behavior of Batocera horsfieldi (Hope) was observed in the laboratory. The results showed that copulation of this longhorned beetle consisted of three phases: (i) encountering and pair-bonding; (ii) mating attempt and ejaculation; and (iii) post-copulatory guarding. Frozen females, with cuticular hydrocarbons stripped by hexane extraction, showed no attraction for males. Reapplying the solvent extract of frozen females to both washed dead males and females caused mating attempts by males, confirming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…As regards mating behaviour of B. horsfieldi , males show some mating‐attempt behaviours, including licking the maxillary palps and labial palps repeatedly and abdominal bending. This licking has been suggested to be related to contact sex pheromones (Luo et al. 2011).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As regards mating behaviour of B. horsfieldi , males show some mating‐attempt behaviours, including licking the maxillary palps and labial palps repeatedly and abdominal bending. This licking has been suggested to be related to contact sex pheromones (Luo et al. 2011).…”
Section: Discussionmentioning
confidence: 87%
“…2010). Chemical cues (contact sex pheromones) also play an important role in the recognition of females by male B. horsfieldi (Luo et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Male B. horsfieldi displays a dashing behaviour for short‐range mate location, and previous studies have suggested that pheromones might be involved in this behaviour for this beetle species (Luo et al. ). Similar sex‐biased expression patterns of OBPs were also found in other insect species, such as SexiOBP2‐4 and SexiOBP10 of Spodoptera exigua (Zhu et al.…”
Section: Discussionmentioning
confidence: 90%
“…High level of BhorOBP2 expression in antennae of males on day 5 post‐eclosion might reflect the role for BhorOBP2 in mate‐seeking behaviour. Mating behaviour has been observed among female and male B. horsfieldi 5 days after emergence (Luo ). High levels of OBP expression in the early developmental stages of unmated males might be involved in locating suitable mates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation